PEMBELAJARAN KOOPERATIF MODEL TWO STAY TWO STRAY WITH QUESTION ROLL UNTUK MENINGKATKAN HASIL BELAJAR SISWA di SMPN II SINGOSARI MALANG - Asmarani, Dewi (Jurnal Dinamika Penelitian: Media Komunikasi Penelitian Sosial Keagamaan, 2017)
This study describes the Cooperative Learning Two Stay Two Stray with question roll models to improve the learning outcomes of students at class VII SMPN II Singosari Malang on statistical material. This research is qualitative with classroom action research (PTK). Data collection techniques used are direct observation techniques, test, and field remarks. Analysis of data using qualitative analysis and ways percentage. The results showed that through a cooperative learning Two Stay Two Stray with question roll models obtained significant development in which the average score and the percentage of mastery learning of the preliminary data, the first cycle and the second cycle. The average score obtained results (59.86, 76.73 and 85.95) and the completeness of classical study is 53.65%, 75% and 92.5%. Thus it can be concluded that cooperative learning Two Stay Two Stray with question roll models can improve learning outcomes Math class VII SMPN II Singosari Malang